Correlation among Construction, Safety, Accident, and the Effectiveness Construction Industry Development Board (CIDB) Green Card Training Program: An Initial Review - Wahab, Nurhana Abd; Mahmood, Nik Hasnaa Nik; Minghat, Asnul Dahar (ASEAN Journal of Science and Engineering, 2023)
The objective of this study was to show the correlation between construction, safety, accident, and the effectiveness Construction Industry Development Board (CIDB) Green Card Training Program. This paper was based on a literature review to get an explanation. This study can be used for reference for informing the need in taking care of possible risks and safety in the industry.